Cognitive behaviour therapy for eating disorders: a "transdiagnostic" theory and treatment. - Fairburn, C; Cooper, Z; Shafran, R (2003)
This paper is concerned with the psychopathological processes that account for the persistence of severe eating disorders. Two separate but interrelated lines of argument are developed. One is that the leading evidence-based theory of the maintenance of eating disorders, the cognitive behavioural theory of bulimia nervosa, should be extended in its focus to embrace four additional maintaining mechanisms. Specifically, we propose that in certain patients one or more of four additional maintaining processes interact with the core eating disorder maintaining mechanisms and that when this occurs it is an obstacle to change. The additional maintaining processes concern the influence of clinical perfectionism, core low self-esteem, mood intolerance and interpersonal difficulties. The second line of argument is that in the case of eating disorders shared, but distinctive, clinical features tend to be maintained by similar psychopathological processes. Accordingly, we suggest that common mechanisms are involved in the persistence of bulimia nervosa, anorexia nervosa and the atypical eating disorders. Together, these two lines of argument lead us to propose a new transdiagnostic theory of the maintenance of the full range of eating disorders, a theory which embraces a broader range of maintaining mechanisms than the current theory concerning bulimia nervosa. In the final sections of the paper we describe a transdiagnostic treatment derived from the new theory, and we consider in principle the broader relevance of transdiagnostic theories of maintenance.